(untitled) (Research, Society and Development, 2020)
To reflect on the relationship between pregnant women / women who use crack cocaine and professionals working in health institutions, from which we seek to understand why these institutions pose a threat to these women. This is a theoretical essay originated from the reflections and questions about the way some pregnant women / women who are crack users who participated in a study developed in 2015, about their relationship with professionals working in health institutions. These pregnant women / puerperal women were hospitalized in two maternity hospitals in two municipalities, one in the far south and the other in the northeast region of Brazil. The Law of Copyright was respected by making the appropriate references. We obtained as a result three sections, first section describes the reasons that lead professionals to relate to pregnant women / postpartum women. Then the theoretical basis of the study is presented. Finally, the reflections on the threats that represent the institutions for these women. Pregnant women who use crack when being treated at health services suffer stigmatization / labeling, which is reflected directly in their self-image, which can have serious consequences, including removing them from health services, due to discriminatory attitudes. It also generates low self-esteem feelings of disability and disbelief in life and recovery goals.